CORPORATE SOCIAL RESPONSIBILITY PERUSAHAAN KEPADA MASYARAKAT STUDI KASUS PADA PT GOLD COIN SPECIALITIES - Nurma Risa; Tuti Sulastri; Joko Pramono (JRAK: Journal of Accounting Research and Computerized Accounting, 2011)
The purpose of this study is to provide a real picture of the company's image from the point of view of the surrounding community as a result of the implementation of CSR programs and business operations of the company towards its stakeholders, particularly to residents around the company. This study used a qualitative approach, with descriptive-qualitative method.This research will be directed descriptive to find out CSR programs conducted by PT GCS, which has a direct impact to the community around the company. Then the survey was also carried out to communities around the company to see what the community regarding CSR PT GCS program, which includes welfare and community satisfaction, community participation in CSR programs, as well as the image of the company according to the community. The results show, it turns out the company has no specific CSR programs. Giving grants for religious activities and posyandu are recognize as company's CSR activities. However, communities around company are not satisfied with what the company has done, especially in the form of environmental pollution of air pollution that is odor and dust that sometimes interfere community activities. While the company considers the pollution is coming from leaks in the production process and is not a serious problem. This problem led to disharmony between communities and companies that lead to prolonged conflict and the community gives a bad image to the company. For advice, company needs to review the concept of CSR and formulate more precisely what and how their relationships with the community will be built. In addition, society itself seems also to be invited participation in designing CSR programs. With so expected dissemination and implementation of new concepts that CSR can occur in a good partnership between the companies with the community.